The Results of experimental infection of Cryptosporidium spp. in BALB/c mice (Mongolian Journal of Agricultural Sciences, 2021)
Cryptosporidium is a small protozoan parasite that infects the microvillous region of epithelial cells in the digestive and respiratory tract of vertebrates. It is an obligate intracellular parasite of man and other mammals, birds, reptiles and fish. We were purification Cryptosporidium spp. oocysts with saturated sugar solution from diarrhea cattle. And experimental infection use by control C. parvum (Germany) strain and Cryptosporidium spp. with oral 1x107 oocyst/ml doses in per BALB/c mouse. Post inoculation detected Cryptosporidium oocysts within a week in the feces mice and counted average Cryptosporidium spp. (Mongolia) 1.033±0.2x106 (p